Biochar from Pine cone (strobilus of Pinus elliottii) by torrefaction process: evaluation of the adsorptive and energy capacity - da Silva, Matheus Antonio [UNESP]; Dias, Diogenes dos Santos; Capela, Jorge Manuel Vieira [UNESP]; Fertonani, Ieda Aparecida Pastre [UNESP]; Ribeiro, Clovis Augusto [UNESP] (Springer Nature, 2023)
Using biomass residues of any nature has gained more and more importance over time. In this work, the adsorptive and energetic capacity of biochar produced from a dry pine cone or strobilus residues of Pinus elliottii by torrefaction in the range of 200 and 300 ∘ C was evaluated. Raw strobilus pellets (P0) and their biochars (P200 to P300) were produced by two distinct routes of obtaining and then assessed for integrity in the water, thermal stability by TG/DTG and DTA, and composition by proximate, ultimate analysis, and ATR-FTIR spectra. As for energy use, the HHV ranged from 18.5 to 22.3 MJ kg - 1 from P0 to P300. In addition, other energy parameters such as mass and energy yields (MY and EY), enhancement factor (EF), energy-mass co-benefit index (EMCI), severity factor (SF), and torrefaction severity index (TSI) were evaluated. The reduction of MY from P200 to P260 was 14.4%, while for EY, it was 9.2%. About P300, the decline was 34.6 and 25.3% for MY and EY, respectively. Adsorption isotherms showed favorable interaction between methylene blue (MB) and biochars, with the best values for biochars being P220 to P260. All adsorption isotherms are L-type, indicating physical adsorption in low-porosity solids that tend to form multilayers. However, with the increase in torrefaction temperature, there was a decrease in functional groups on the biochar surface, increasing its hydrophobicity and decreasing the adsorption capacity of MB. To better elucidate the adsorptive process of biochars, isothermal models such as Langmuir, Freundlich, DRK, and Temkin were applied and evaluated. Results indicated P260 with better use as an adsorbent and subsequent energy use.
Keywords: Adsorptive capacity; Biochar; Energy capacity; Isothermal models; Pine cone